2005
DOI: 10.1124/jpet.105.090597
|View full text |Cite
|
Sign up to set email alerts
|

Induction of β3-Adrenergic Receptor Functional Expression following Chronic Stimulation with Noradrenaline in Neonatal Rat Cardiomyocytes

Abstract: This study aimed to characterize ␤ 3 -adrenergic receptors (ARs) in rat neonatal cardiomyocytes using the noradrenaline (NOR) properties to modulate the expression and function of the three ␤-ARs. We assessed the effect of NOR (physiological nonselective agonist), isoprenaline (ISO, ␤-nonselective agonist), dobutamine (DOB, ␤ 1 -selective agonist), and procaterol (PROC, ␤ 2 -selective agonist) on cAMP accumulation using cardiomyocytes untreated or treated with 100 M NOR for 24 h. The inhibition of forskolin-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 32 publications
4
47
0
1
Order By: Relevance
“…Contrary to ␤ 1 -AR (and to a lesser extent ␤ 2 -AR), the abundance of ␤ 3 -AR messenger ribonucleic acid (and proteins) increases in ventricular myocardium from patients with heart failure from ischemic or dilated cardiomyopathies (19), as well as sepsis (20). Such paradoxical regulation is consistent with in vitro up-regulation of ␤ 3 -ARs in rodent cardiomyocytes chronically exposed to catecholamines (21), as well as animal models of diabetes (22), a condition also associated with hyperadrenergism. Also, ␤ 3 -ARs are more resistant (than ␤ 1 -and ␤ 2 -ARs) to homologous desensitization (23).…”
supporting
confidence: 57%
“…Contrary to ␤ 1 -AR (and to a lesser extent ␤ 2 -AR), the abundance of ␤ 3 -AR messenger ribonucleic acid (and proteins) increases in ventricular myocardium from patients with heart failure from ischemic or dilated cardiomyopathies (19), as well as sepsis (20). Such paradoxical regulation is consistent with in vitro up-regulation of ␤ 3 -ARs in rodent cardiomyocytes chronically exposed to catecholamines (21), as well as animal models of diabetes (22), a condition also associated with hyperadrenergism. Also, ␤ 3 -ARs are more resistant (than ␤ 1 -and ␤ 2 -ARs) to homologous desensitization (23).…”
supporting
confidence: 57%
“…TRITC-conjugated anti-rabbit IgG were from Beijing Zhongshan Golden Bridge Biotechnology (Beijing, China). The doses of ISO, propranolol, ICI 118551, CGP20712A, PTX, H89, clenbuterol were used according to the international concentra tion [10,13] .…”
Section: Methodsmentioning
confidence: 99%
“…Responses to sympathetic activation are mediated through the action of the endogenous catecholamines norepinephrine and epinephrine on adrenergic receptors (ARs). The heart expresses all three subtypes of β-AR, as well as three types of α 1 -AR: α 1A -AR, α 1B -AR, and α 1D -AR [10] . A recent report demonstrated that α-adrenergic receptor agonist phenylephrine enhanced Cx43 expression, but not Cx40 and Cx45 expression, in neonatal rat cardiac myocytes (NRCMs), resulting in enhanced gap-junction conductance.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that after short-term exhaustive exercise, characterized by increased plasma CAs, increased ␤ 2 -AR expression and density was observed in human peripheral lymphocytes [29,30] . In addition, ␤ 3 -ARs were shown to be upregulated in rat neonatal cardiomyocytes following chronic exposure to noradrenaline [31] . The ␤ 1 -AR overexpression has been detected in peripheral lymphocytes of hypertensive and cardiac patients [18,19] that are often associated with higher plasma CAs [32,33] .…”
Section: Discussionmentioning
confidence: 99%